Pola Asuh Demokratis dan Kecerdasan Emosional dengan Prestasi Belajar Siswa-Siswi SMP Bilingual - Rahayu, Sesanti; Hendrati, Fabiola (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
This study aimed to analyze the relationship tendency democraticparenting and emotional intelligence and academic achievement Bilingual juniorstudents. Subject reaserch are 124 male and female students grade 7 juniorBilingual tepadu Junwangi-Krian. The implementation of data collection is done injunior high school student and Bilingual Integrated. Distributed measurement scaleconsists of two questionnaires: 1) Democracy parenting scale, 2) emotionalintelligence scale. The result show F regression = 2.898 de-ngan p = 0.059 (p>0.05) , this means that there is no significant relationship between democraticparenting and emotional maturity with Academic Achievement.Keywords : learning achievement, parenting Democracy, emotional intelligence